Pengaruh financial literacy dan financial inclusion terhadap kinerja UMKM - Tri Nova Ningsih; Abel Tasman (Jurnal Kajian Manajemen dan Wirausaha, 2020)
This study aims to test and empirically prove the effect of financial literacy, financial inclusion, and internal locus of control on the performance of MSMEs (micro, small, and medium enterprise) in Padang City. The object of this study is the MSMEs in the city of Padang. The number of samples is 399 respondents of MSME business operators, the sample selection uses random sampling, hypothesis testing is done by using multiple regression analysis and tested using the SPSS version 20.0 application. The results of the study indicate that financial literacy, financial inclusion, and internal locus of control have a positive and significant effect on MSME performance.